The ethics of AI creativity: emerging challenges - Ahmed, Iman Osman Mukhtar; Hassan Abdalla Hashim, Aisha; Ahmed, Zeinab E; Sophian, Ali (Kolej Komuniti Sungai Siput, 2024)
The utilization of Artificial Intelligence (AI) in educational institutions has the potential to bring about a significant transformation in current educational systems. As more educational establishments incorporate AI tools into their teaching and learning practices, there is a growing adoption of Large Language Model (LLM) technologies, including within the field of education. This adoption is driven by the ever-increasing volume of data and evolving educational requirements. However, despite the advantages offered by these technologies, there remains a consistent lack of clarity surrounding the ethical guidelines, technical standards, and best practices that are vital for their effective implementation. This paper primarily focuses on two key areas of research. Firstly, it seeks to investigate the potential benefits, risks, and outcomes associated with the use of LLM technologies in education. Secondly, it delves into the ethical considerations that should guide the utilization of LLM technologies within this domain. The findings underscore the significance of affording students access to LLM technologies in order to enhance the learning environment, with an emphasis on the necessity of transparent and reliable data collection in research. Moreover, given the considerable potential for the dissemination of misinformation and harmful content through LLM technologies, it is imperative to integrate ethical considerations throughout the field of education. This necessitates educating users and reinforcing measures to control the content in order to mitigate associated risks.